Advantages of liquid nitrogen freezing in long‐term frozen preservation of hairtail (Trichiurus haumela): Enzyme activity, protein structure, and tissue structure. (28th June 2021) - Hu, Lingping; Ying, Yubin; Zhang, Hongwei; Liu, Jialin; Chen, Xin; Shen, Ni; Li, Yujin; Hu, Yaqin
Abstract: This study aimed to investigate the effects of liquid nitrogen freezing (LNF) in long‐term frozen preservation of hairtail. Fresh hairtail was frozen by liquid nitrogen or cold air and stored at −20°C or −80°C for up to 120 days. The contents of carbonyl, TCA‐soluble peptides, AG and NAG enzyme activities increased, whereas Ca 2+ ‐ATPase, Mg 2+ ‐ATPase activity and the contents of sulfhydryl group decreased with the storage time increased. The activities of cathepsin B and B + L could be inhibited by low temperatures in the initial 40 days. However, the inhibition gradually weakened as the storage time increased. Protein surface hydrophobicity increased and reached a peak of 480.23 on day 60 with a subsequent fluctuant decrease. The α‐helix and β‐sheet structures of myofibrillar protein decreased, while the β‐turn and random coil structures increased. And the texture degradation occurred in all the tested four groups. The muscle fibers begun to break in cold air freezing (CAF) group after storage of 60 days. After a storage period of 120 days, large holes appeared in meat sample of CAF group. The muscle fibers of the LNF groups were kept much more complete than that of the CAF groups, indicating the advantages of LNF. Practical Application: In this study, the advantages of liquid nitrogen freezing (LNF) on the quality of hairtail during long‐term frozen preservation were showed by enzyme activity, protein structure and tissue structure. Although LNF causes inevasible damage to the fish meat, the ice crystals during freezing were rather small and distributed homogenously due to fast freezing rate. Thus, the mechanical damage to muscle was much lower than that of the cold air freezing (CAF), showing great advantages of LNF. Liquid nitrogen was recommended for pre‐frozen of hairtail before frozen storage to maintain the quality of hairtail. These results could provide theoretical guidance for the applying of LNF on the hairtail processing for the quality maintenance of hairtail whilst aiming to get maximum nutritional benefits. This knowledge can also be widely applicated in other fishery products preservation. Abstract :